Nalar Fiqh NU Pasca Munas Alim Ulama1992: Arah Baru Menuju Madhhab Manhaji - Luthfi Hadi Aminuddin (Justicia Islamica, 2008)
This study aims to examine the development of the fiqh reasoning of Nahdlatul Ulama (NU) after the 1992 Alim Ulama National Conference, which marked a paradigm shift from the qauli madhhab to the manhaji madhhab. This transformation reflects NU's efforts to respond to socio-contextual challenges with a more open and dynamic methodological approach. This study uses a qualitative method with a literature study approach, analyzing official NU documents, the results of bahtsul masail, and literature related to manhaji fiqh. The results show that NU has begun to prioritize the principles of maqashid syariah, maslahah, and a contextual approach in making law, without abandoning the roots of the madhhab tradition. This change directs NU fiqh towards a pattern of thinking that is more solution-oriented, inclusive, and adaptive to the times. This study emphasizes the importance of the madhhab manhaji as a framework for istinbath of law that is relevant to contemporary society.